Effective removal of crystal violet and methylene blue dyes from water by surface functionalized zirconium silicate nanocomposite. Issue 2 (April 2019) - Mahmoud, Mohamed E.; Nabil, Gehan M.; Khalifa, Mohamed A.; El-Mallah, Nabila M.; Hassouba, Hind M.
Abstract: Organic dyes derivatives are well characterized as carcinogenic, toxic and hazardous materials. The presence of low concentration levels of dyes in water (ppm or even ppb) may cause severe changes in the physical appearance of water. Therefore, removal of dyes from water represents a great challenge of finding the most efficient methodology. For this reason, zirconium silicate nanoparticles [ZrSiO4 NPs] were used to assemble a new nanomaterial based on surface modification with SDS to produce [ZrSiO4 NPs -SDS] as an efficient nanocomposite for removal of two cationic dyestuffs; viz. crystal violet (CV) and methylene blue (MB) from water. The SEM, TGA, XRD, FT-IR, HR-TEM and surface area analyses are used to elucidate the surface morphology of ZrSiO4 -SDS nanocomposite. Various adjustable parameters such as pH, nanocomposite mass, contact time, interfering salts and reaction temperature were also studied. The optimum value of pH was recorded to be 2 and 10 for CV, while at pH 1 and 10 for MB dyes. The observed removal values were recorded as 94.8, 96.8 and 97.9% at pH 2 and 95.8, 96.5 and 97.5% at pH 10 for CV using 20, 30 and 40 mg L −1, respectively. Different adsorption isotherms and kinetic models were applied and the best fitting was with the pseudo -second order kinetic model. The thermodynamic parameters revealed that the reactions were spontaneous and exothermic. Finally, 5.0 mg of the nanocomposite was applied for adsorptive removal of CV and MB from real water specimens, with percentage recoveries in the range 85.2–96.14% and 83.31–94.26%, respectively.